Strategi Alokasi Tenaga Kerja Rumahtangga Petani Padi Di Lahan Rawa Lebak Untuk Peningkatan Pendapatan Dan Mengurangi Tingkat Kemiskinan - Muhammad Fauzi Makki (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
This article analyzes how the household labor allocation strategy of paddy farmers in lebak swampland. The analysis is based on the time allocation theory by Becker in the form of decision-making for on-farm activities (paddy farming and non-paddy farming); off-farm and non-farm. The respondents of the research is 100 paddy farmers of lebak swampland. The result of analysis shows that non-paddy farming activities (fishery and rising Alabio duck) and non-farm activities provide most remuneration, thus providing the opportunities to increase the income and poverty alleviation. Therefore, household labor allocation strategy of farmers should be directed at these two activities. Paddy farming only to fulfill food needs of the family alone.